Implementasi Metode VIsekriterijumsko KOmpromisno Rangiranje dalam Sistem Pendukung Keputusan Identifikasi Keluarga Berisiko Stunting - Nurul Ilma Hasana Kunio (Komputika : Jurnal Sistem Komputer, 2026)
Stunting remains a significant chronic nutritional problem in Palembang City, where the identification and management of families at risk of stunting are still conducted manually, potentially leading to inaccuracies and delays in decision-making. This condition results in suboptimal interventions for the targeted families. This study utilizes a dataset comprising 400 families obtained from the Palembang City Office of Population and Family Planning (DPPKB) in 2024 as the basis for developing a Decision Support System (DSS). The method applied is VIse Kriterijumska Optimizacija Kompromisno Resenje (VIKOR), one of the approaches in Multi-Criteria Decision Making (MCDM) that can objectively integrate various risk-determining factors. The main criteria used include sources of drinking water, sanitation facilities, categories of couples of childbearing age, and participation in the Family Planning program. The results show that the family coded E obtained the highest index value of 1.00, categorized as high stunting risk, while the family coded B scored 0.00, indicating a low-risk level. The developed system is capable of providing more accurate and objective rankings of at-risk families, thereby assisting the DPPKB in determining precise intervention priorities. Thus, the implementation of the VIKOR method in this decision support system makes an important contribution to enhancing the effectiveness of stunting reduction acceleration programs in Palembang City. The contribution of this research lies in the application of the VIKOR method to support data-driven policies for accelerating stunting reduction in Palembang City.